2010
DOI: 10.1016/j.jphotochem.2010.07.008
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic bleaching of p-nitrosodimethylaniline and a comparison to the performance of other AOP technologies

Abstract: a b s t r a c tIn this paper, the performance of a developed photo reactor has been studied using the process of bleaching of p-nitrosodimethylaniline (RNO). The effect of available surface area in the reactor has been tested with the TiO 2 suspension system as reference, as well as the influence of operating parameters as pH and aerobic/anaerobic conditions. The bleaching of RNO by UV light alone was found to be significantly slower compared to the bleaching observed when applying photocatalysis, but the init… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 81 publications
(33 citation statements)
references
References 20 publications
2
31
0
Order By: Relevance
“…In the present study, OH radical generation was also investigated (Fig. 4(a–d)) by monitoring the bleaching of p -nitrosodimethylaniline (PNDA) as the intensity of the characteristic absorption peak at λ = 440 nm decreased3233. These results confirm the photochemical reactions proposed for the SPSC process, in which H 2 gas and OH radicals were generated during the photo-assisted growth of ZnO nanorods.…”
Section: Discussionsupporting
confidence: 78%
“…In the present study, OH radical generation was also investigated (Fig. 4(a–d)) by monitoring the bleaching of p -nitrosodimethylaniline (PNDA) as the intensity of the characteristic absorption peak at λ = 440 nm decreased3233. These results confirm the photochemical reactions proposed for the SPSC process, in which H 2 gas and OH radicals were generated during the photo-assisted growth of ZnO nanorods.…”
Section: Discussionsupporting
confidence: 78%
“…13 is mainly carried out in sulfuric acid solutions under carefully monitored conditions, and the RNO bleaching efficiency of persulphate is insignificant. Finally, reduction of RNO has in a study of photocatalytic bleaching of RNO been showed to be a fast pathway for color removal in aqueous solution [31]. In the one-compartment cell, reductive bleaching of RNO may be achieved at the Si-BDD cathode and can be the most likely candidate for the baseline bleaching.…”
Section: Electrochemical Bleaching Of Rno In the Presence Of A Hydroxmentioning
confidence: 99%
“…Another example is the use of quinoline, which led to the formation of numerous products until their complete mineralization in photo‐Fenton and photocatalysis systems . Moreover, compounds such as p‐Nitrosodimethylaniline (RNO) (reaction ) and 1,5‐diphenyl carbazide (DPCI, reaction ) react with other ROS pointing out the need to add scavengers to quantitatively measure the concentration of each ROS specie. …”
Section: Determination Of Reactive Oxygen Species Involved In Advancementioning
confidence: 99%